A visual programming approach for teaching cognitive modelling - Collins, Trevor D.; Fung, Pat (Computers and education, 2002)
This paper describes an investigation into the use of a visual programming language to teach computer-based modelling to undergraduate cognitive psychology students. Four sets of evaluation studies were carried out. The findings of these theoretical and empirical evaluations are related to the design principles that informed the language and the context in which it was examined. The educational benefits of gaining some practical experience of cognitive modelling where highlighted in these studies, as was the importance of introducing the visual language within a sound teaching framework. The comments of the students and tutors regarding the use of the Hank visual programming language to teach cognitive modelling indicate that Hank avoids some of the syntactic problems associated with textual programming languages, it can be used to illustrate the flow of control during a program's execution, and it is intuitive and easy to use